Bio efficacy of frog skin bacteria as biological control agents against chili anthracnose disease - Susilawati, Lela; Sari, P. Afrizka; Septiani, Maulana; Purnomo, E.S. (Jurnal Biologi Udayana; Vol 27 No 1 (2023): JURNAL BIOLOGI UDAYANA, 2023)
Amphibian skin e.g., frog carry bacterial symbionts on their skin that protect the frog from invasion of pathogen infection. This study aimed to evaluate antifungal activity of five bacterial skin frog (namely KSMD3; KSMD9; KSMD10; KSMV12; KSMV15) of Indonesian origin, Fejervarya limnocharis, against phytopathogen ( Colletotrichum capsici) TCKr2. Primary screening for their antifungal activity was performed using dual culture method on nutrient agar contained 2% (w/v) of dextrose. The alteration of hyphal morphology on media and the detached chili fruit bioassay were observed. Isolate of KSMD3 was selected based on its significant performance in inhibiting the growth of the chili anthracnose pathogen, C. capsici . In addition, the KSMD3 showed low severity of disease incidence on detached chili fruit. Based on the analysis of 16S rDNA, the isolate of KSMD3 was identified as member of genera of Pseudomonas .